Effect of Psidium guineese Sw. leaf extract and coconut cake extract on serum lipid profiles and serum antioxidant capacity of Wistar rats - Senanayake, C.M.; Seneviratne, K.N.; Jayathilaka, N.; Ekanayaka, S. (My University, 2017)
Attached